Tradisi Pembacaan Qulhu Tiga Malam Selepas Kepergian Mayit Tinjauan Studi Living Qur’an - Devi Yanti Rambe; Hafizzullah Hafizzullah (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2022)
There are verses of the Qur'an that live in the community of Kotapinang District, South Labuhanbatu Regency, North Sumatra Province, this tradition has been carried out by the community for generations, where the tradition is in the form of a tradition of reading qulhu three nights after the departure of the dead in a death ritual. The aims of this study are: To describe the practice of reciting qulhu three nights after the death of the deceased. The type of research used is field research or (field research). with a phenomenological approach. Then the data collection techniques are interviews, observation and documentation. The results show that, the practice of carrying out the tradition of reading qulhu three nights after the departure of the deceased has variations, basically for the verses / surahs that are read the same as well as additional readings in addition to the verses that are read, it's just that the placement of the readings is different every night.